Electrical, photoconductive, and photovoltaic characteristics of a Bi2Se3 3D insulator based metal-insulator-semiconductor diode - Ocaya, Richard O.; Al-Sehemi, Abdullah G.; Dere, Aysegul; Al-Ghamdi, Ahmed A.; Yakuphanog, Fahrettin (Elsevier Science Sa, 2022)
A metal-insulator-semiconductor (MIS) diode based on the Bi2Se3 3D topological insulator on p-Si substrate was fabricated for use as a photodiode with the Al/p-Si/Bi2Se3/Al structure. The current-voltage, series resistance, and impedance characteristics were investigated using standard techniques and a new series resistance compensated method. The application of the method is described in a brief algorithm. The diode exhibits an apparent rectification ratio of 3700 and the R-s compensated rectification ratio that is almost 1.5 times higher, thus suggesting a new method to determine the true rectification ratio of a diode. The diodes have an ideality factor greater than unity, a barrier height of 0.647 eV, and a built-in potential of 0.476 V. The maximum density of the interface state of the diode is 5.1 x 10(12) eV(-1)cm(- 2) over the reverse bias range of -3-0 V. This is comparable to those of oxide-based diodes, but unexpected since oxygen-induced defect states were thought unlikely. When compensating for the effects of series resistance, the dark current of the diode is found to be 2.5 nA. The open-circuit voltage of the diode was estimated at around 0.244 V at 100 mW/cm(2) solar light illumination, with an estimated efficiency of at most 2.9%. These values are typically reported bismuth-based topological insulator/Si diodes. This shows that the diode can be used as a low-power solar cell. The photoresponses of the device show that it is suitable as a fast MIS photodiode over a wide range of incident intensity.
Keywords: Topological insulator; Bismuth selenide; Series resistance compensation; Schottky diode; Photodiode; Solar cell